IMPLEMENTATION OF DIGITAL MARKETING STRATEGIES IN EFFORTS TO IMPROVE SUSTAINABLE BUSINESS PERFORMANCE - rubson; Nuraeni Kadir (Scientia Integritas Utama, 2023)
The increasing use of social networks and the way their users communicate with companies on the Internet has given rise to new business models based on two-way communication between companies and Internet users. This study aims to find a model for implementing digital marketing strategies in an effort to improve sustainable business performance. In addition, this study is also to describe the digital marketing strategy carried out by MSME business actors. This research is a combined research (mix methods). Data was collected through questionnaires and in-depth interviews. Furthermore, quantitative data were analyzed to find a structural equation modeling (SEM) model, while qualitative data were analyzed descriptively. The research results confirm that digital marketing strategies can improve sustainable business performance. Digital marketing strategies are widely used by MSME business actors. These include presence on major social media platforms as well as email, SMS, search engine optimization and messaging apps such as Telegram, Facebook Masengger, Instagram and Whatsapp.